PERFORMANCE CHARACTERISTICS MODEL OF A THIN LEAD ZIRCONATE TITANATE DISC UNDER DIFFERENT CONDITIONS - Pasha, R. A.; Zaman, M. Z. (The Nucleus, 2012)
In the present work a thin lead zirconate titanate (PZT) piezoelectric ceramics disc investigated for its sensitivity in performance at two different temperatures for different frequencies and at a series of resistance bands. The peak-peak voltage has been considered as its output functioning parameter at different conditions. Real time data was collected by connecting the prescribed circuitry and behavior of material investigated for ten consecutive resistance bands. The disc was found highly sensitive to the selected range of frequencies and resistances as compared with temperature sensitivity. Experimental results have been used to develop a mathematical model by considering the ten consecutive resistance bands for two referenced temperatures. An exponential behavior has been noted which indicated the change at higher values of resistance bands. The behavior of the material was founded with the stated frequencies and resistance bands at room temperature and at 1600C.